The impact of neighborhood socioeconomic status on retention in care and viral suppression among people living with HIV. Issue 11 (2nd November 2022) - López, Julia D.; Qiao, Qisha; Presti, Rachel M.; Hammer, Rachel A.; Foraker, Randi E.
ABSTRACT: Our study combined publicly available neighborhood socioeconomic status (nSES) data from the U.S. Census and clinical data to investigate the relationships between nSES, retention in care (RIC) and viral suppression (VS). Data from 2275 patients were extracted from 2009 to 2015 from a midwestern infectious diseases clinic. RIC was defined as patients who kept ≥ 3 visits and VS as an average viral load <200 copies/mL during their index year of study. Logistic regression models provided estimates for neighborhood-level and patient-level variables. In multivariable models, patients living in zip codes with low disability rates (1.50, 1.30–1.70), who wereolder (1.02, 1.01–1.03), and receiving antiretroviral therapy (ART; 3.81, 3.56–4.05) were more likely to have RIC, while those who were unemployed (0.72, 0.45–0.98) and self-reported as BIPOC (0.79, 0.64–0.97) were less likely to have RIC. None of the nSES variables were significantly associated with VS in multivariable models, yet older age (1.05, 1.04–1.05) and self-reported as BIPOC (1.68, 1.36–2.09) were modestly associated with VS, and receiving ART (6.14, 5.86–6.42) was a strong predictor of VS. In multivariable models, nSES variables were independently predictive more than of patient-level variables, for RIC but not VS.